KATA TUGAS YANG MENYERTAI VERBA DAN NOMINA DALAM BAHASA ARAB (Analisis Semantik dan Sintaksis) - , HASANATUL HAMIDAH, Prof. Dr. Syamsul Hadi, S.U, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This Thesis writing is focused on semantic and syntactic analysis of the function word that accompany the words and clauses form of nouns and verbs . This study is done in an effort to reveal the form of the function word that can accompany verbs and nouns and express meanings that was tagged. In addition, this study also reveals the function, position and the case of each word in a sentence task The research is a form of sinkronis, observational study with the object of study in a specified period. Sources of data used in this reseach are review of the verses of Al - Quran as well as the following books